Evolution trend and hot topic measurement of climate migration research under the influence of climate change - Liang, Bing; Shi, Guoqing; Sun, Zhonggen; Babul, Hossain; Zhou, Min (Frontiers in Ecology and Evolution, 2023)
Introduction Global climate change, which is characterized by climate warming, has become one of the most prominent risk problems in society at present. Climate migration brings many accompanying problems to the environment, economy, politics, society, and culture. It is of great theoretical and practical significance to study the internal relationship between climate change and population migration. Methods The data were extracted from the Web of Science core collection database (WOS) and China Knowledge Network database (CNKI). A total of 785 documents and 157 documents in the field of climate migration from 2008 to 2021 were selected as analysis samples. Word frequency analysis, clustering analysis, sudden word detection analysis, and other methods were extensively used to build the evolution trend map of climate migration using CiteSpace visual bibliometric software. Results It is concluded that climate migration research has experienced three stages of development: initial exploration stage (2008-2011), development enrichment stage (2012-2017), and system deepening stage (2018).The hot topics of climate migration include: (1) different types of climate migration research; (2) Quantitative model research on climate migration; (3) Climate justice research. Different types of climate migration include 7 main types: (1) migration caused by sea level rise; (2) Resettlement caused by flood disaster; (3) Migration due to worsening drought; (4) Migration caused by extreme climate events; (5) Voluntary migration due to climate change discomfort; (6) Project resettlement caused by climate change response engineering measures; (7) Migrants whose livelihoods are broken due to climate change. Discussion The study points out that climate migration research is an interdisciplinary research field, which needs joint research by scholars from different academic backgrounds. In the future climate migration research, 1) strengthen the prediction ability of climate change population migration model; 2) Make use of China’s beneficial exploration in the migration fields such as engineering resettlement, ecological resettlement and poverty alleviation resettlement to formulate climate migration policies, regulations and strategic planning; 3) Establish a database cloud platform related to climate change and population migration; 4) Strengthen the exchange and cooperation between Chinese researchers in the field of climate migration and international scientific research institutions.